Emmanuel Levinas and the Politics of Non-Violence - Tahmasebi-Birgani, Victoria, 1961- (Book collections on Project MUSE., 2014)
In this book, Victoria Tahmasebi-Birgani provides the first examination of the applicability of Emmanuel Levinas' work to social and political movements.